2016
DOI: 10.1109/lpt.2016.2580604
|View full text |Cite
|
Sign up to set email alerts
|

Switchable Dual-Wavelength Mode-Locking of Thulium-Doped Fiber Laser Based on SWNTs

Abstract: We experimentally demonstrate switchable dual-wavelength mode-locking of thulium-doped fiber laser (TDFL), using single-wall carbon nanotubes (SWNTs) as saturable absorber (SA). Due to the cavity birefringence-induced comb filter, switchable mode-locking can be individually realized for the proposed TDFL among three wavelengths of 1947 nm, 1945 nm, and 1943 nm, with almost the same 3-dB spectral bandwidth of 2.2 nm, repetition rate of 13.6 MHz and pulse-width of 1.8 ps. Furthermore, after finely adjusting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Because of their potential to broaden the channel capacity of communication systems, the development of multi-wavelength lasers near the 2-μm waveband has attracted particular research attention [4][5][6]. Using thulium-doped fiber as a gain medium, a laser can be excited in the 2-μm band with a higher self-focusing threshold and lower nonlinear effect than in the nearinfrared band [7,8]. Such a laser poses little risk to the eyes and finds applications in various fields, including laser radar, laser communication, and environmental remote sensing [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Because of their potential to broaden the channel capacity of communication systems, the development of multi-wavelength lasers near the 2-μm waveband has attracted particular research attention [4][5][6]. Using thulium-doped fiber as a gain medium, a laser can be excited in the 2-μm band with a higher self-focusing threshold and lower nonlinear effect than in the nearinfrared band [7,8]. Such a laser poses little risk to the eyes and finds applications in various fields, including laser radar, laser communication, and environmental remote sensing [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[1] At present, passively mode-locked TDFLs incorporating an artificial or real saturable absorber (SA) have been primarily used as novel laser sources. [2][3][4][5][6][7][8][9][10][11] Among these mode-locking techniques, nonlinear polarization rotation (NPR) [2] and nonlinear amplification loop mirror (NALM) [3] mode-locking have the characteristic of a high damage threshold but are extremely sensitive to environmental fluctuations. Usually, such drawbacks are not desirable in applications of medical treatment and scientific research.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, such drawbacks are not desirable in applications of medical treatment and scientific research. Recently, graphene, [4][5][6][7] carbon nanotubes (CNTs), [8] transition metal dichalcogenides (TMDs), [9] topological insulators (TIs), [10] and black phosphorus [11] are being considered as a kind of potential SA for passively mode-locked TDFL. Among them, graphene has become the focus of attention from many researchers because of its many features including low saturable absorption threshold, controlled modulation depth, ultrafast recovery time (100 fs-200 fs), wide spectrum range (300 nm-2500 nm), and easy integration with optical system, which make it stand out in all kinds of mode-locking materials.…”
Section: Introductionmentioning
confidence: 99%
“…Different passively mode locking methods have been explored to generate ultra-short pulses, such as nonlinear polarization rotation technique, [1] semiconductor saturable absorber mirrors, [2,3] single-wall carbon nanotubes, [4] grapheme, [5] and nonlinear optical loop mirrors (NOLMs), [6][7][8] which act as the saturable absorber. He et al presented a laser-diode-pumped passively mode-locked femtosecond disordered crystal laser by using Nd: CaGdAlO 4 (Nd:CGA) as the gain medium.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Jiang et al demonstrated the switchable dual-wavelength mode locking of thulium-doped fiber laser based on SWNTs. [20] Liu et al reported a passively Q-switched Yb:LSO laser based on a tungsten disulphide (WS 2 ) saturable absorber operating at 1034 nm and 1056 nm simultaneously. [21] Bound state solitons in nonlinear optical fiber systems have been reported theoretically and experimentally.…”
Section: Introductionmentioning
confidence: 99%